Customer-based Port Service Quality Model - Kolanović, Ines; Dundović, Čedomir; Jugović, Alen (Promet - Traffic&Transportation, 2012)
This port service quality study is an important precondition for an efficient development of port industry and traffic system as a whole. It is due to the complexity of any port, as a system consisting of a large number of stakeholders rendering services to customers with various requirements, that a unique set of port service quality indices has been still missing. For this reason, the paper explains the port service quality concept in compliance with stakeholders and their requirements within the context of port service quality. The aim of the paper is to present a proposal for a customer-based port service quality model based on empirical study and its reliability testing on a selected sample. The proposed model is defined by five factors and fits satisfactorily into the obtained poll questionnaire results. The statistical data processing package SPSS 16.0 and the LISREL 8.54 programme were used in the study. KEY WORDS: port service, customer, model, factor analysis